Analisis Semiotika Iklan TVC “Aku Ingin Pindah Ke MEIKARTA” - Az Zahra Rachma Kanadia Tohirin; Dwisanto Sayogo (AKSA: Jurnal Desain Komunikasi Visual, 2019)
Indonesian population density is not new problems. From new problem, show up another problem. It is used by various parties to provide a profitable solution whether from public or government. Lippo Grup saw its opportunity to build Mega City Meikarta. One promotion ad titled that have made by Lippo Group “Aku Ingin Pindah ke Meikarta’ have got many negative responses from the public. The purpose of this study was to find out the part that reaped controversy. This study uses the theory of semiotic analysis by Roland Barthes to reveal more details and comparative analysis to see the opposite scene. The result, the study found that the controversy in the form of innuendo by audience because the ad does not offer a sollution in real live and too imaginative. Prospective costumers will face the same problem from reality